2019
DOI: 10.1093/nar/gkz558
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide excision repair of abasic DNA lesions

Abstract: Apurinic/apyrimidinic (AP) sites are a class of highly mutagenic and toxic DNA lesions arising in the genome from a number of exogenous and endogenous sources. Repair of AP lesions takes place predominantly by the base excision pathway (BER). However, among chemically heterogeneous AP lesions formed in DNA, some are resistant to the endonuclease APE1 and thus refractory to BER. Here, we employed two types of reporter constructs accommodating synthetic APE1-resistant AP lesions to investigate the auxiliary repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 63 publications
2
47
0
Order By: Relevance
“…Abasic DNA sites (apurinic/apyrimidinic (AP) sites) are mutagenic and toxic DNA lesions resulting from the loss of nucleobases. 53 AP sites are formed in course of enzymatic repair of damaged DNA or by the influence of external factors. Considering the relevance of AP sites to carcinogenesis, these lesions represent an important analytical and therapeutic target.…”
Section: Supramolecular Dna Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Abasic DNA sites (apurinic/apyrimidinic (AP) sites) are mutagenic and toxic DNA lesions resulting from the loss of nucleobases. 53 AP sites are formed in course of enzymatic repair of damaged DNA or by the influence of external factors. Considering the relevance of AP sites to carcinogenesis, these lesions represent an important analytical and therapeutic target.…”
Section: Supramolecular Dna Sensingmentioning
confidence: 99%
“…Considering the relevance of AP sites to carcinogenesis, these lesions represent an important analytical and therapeutic target. 53,54 In 2018, Y. Shao and co-workers described a supramolecular multicolor DNA sensor for the selective recognition of abasic DNA sites based on the ICA concept with CB [7]. 55 Two natural alkaloids, namely coptisine (21) and palmatine (22) have been used as fluorescent indicators for AP DNA sites (Scheme 3).…”
Section: Supramolecular Dna Sensingmentioning
confidence: 99%
“…This corresponds to the GenBank entries AAB08064 (protein) and U57609 (DNA). The pZAJ_5c vector encoding the functional EGFP protein [33] and the derived pEGFP_Q205* vector carrying the c.613C>T point mutation coding for the non-fluorescent truncated EGFP 1-204 protein, were described previously [30]. The procedure for site-specific incorporation of synthetic oligonucleotides into a single-stranded gap generated in the TS with the Nb.Bpu10I nicking endonuclease (Thermo Fisher Scientific Inc., St. Leon-Rot, Germany) was described previously [30].…”
Section: Reporter Constructs For Detection Of Tmmentioning
confidence: 99%
“…We therefore hoped that an actionable reporter approach would be equally useful for characterization of mutations introduced by DNA TLS. We recently described a new enhanced green fluorescent protein (EGFP) c.613C>T point mutation, which leads to the synthesis of a non-fluorescent EGFP Q205* truncated protein, and showed that any subsequent nucleotide substitution at the affected position results in reversion to a fluorescent phenotype, thus offering a sensitive reporter for detection of TM [30]. Importantly, the mutated base pair in the EGFP Q205* gene is flanked by tandem Bpu10I sites retained from the original EGFP coding sequence.…”
Section: Introductionmentioning
confidence: 99%
“…They are generated by hydrolysis of the N-glycosylic bond between a nucleobase and a deoxyribose 3 , spontaneously or as intermediates in the excision repair of damaged bases. Their repair by dedicated enzymes turns out to be most efficient by base excision repair (BER) but also nucleotide excision repair (NER) 4 . Yet accumulation of AP sites, notably triggered by exogenous oxidative stress, represents a threat for genome integrity.…”
mentioning
confidence: 99%